EFEKTIVITAS TERAPI BERMAIN ORIGAMI DAN MERONCE TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK 5-6 TAHUN DI TK PKK NUSANTARA KABUPATEN PROBOLINGGO : The Effectiveness of Origami and Meronce Play Therapy on Fine Motor Development of Children 5-6 Years in Kindergarten PKK Nusantara Probolinggo Regency - Eka Amelia Firdaus Firdaus; Grido Handoko Sriyono; Nafolion Nur Rahmat (ASSYIFA : Jurnal Ilmu Kesehatan, 2023)
Fine motor skills are skills or abilities to control small or fine muscles to achieve successful skill performance. Children's fine motor skills need to be reminded and developed to prepare children to be ready to write when they enter the academic world (elementary school). This study aims to determine the effectiveness of giving origami therapy and playing meronce therapy at PKK Nusantara Kindergarten in Temenggungan village, Krejengan, Probolinggo. This type of research was a pre-experimental with two group pre-post test design, which is a form of experimental research carried out in two groups. The Population was all children in the Nusantara PKK Kindergarten in Temenggungan village aged (5-6 years) totaling 50 respondents. The instruments used Standart Operating Procedure (SOP) and Modules. Data processed SPSS using the Wilcoxon test. The results showed that the average fine motor value that occurred after being given origami and meronce play therapy was the Wilcoxon Signed Rank Test with a p value =0.000 with a significant level of ρ value <α = 0.005, prepost origami Z value -4.512 while prepost meronce Z value - 4.556, so that it can be stated that playing meronce therapy is more effective on the fine motor development of children in PKK Nusantara Kindergarten in Temenggungan village. This research is expected so that children can develop fine motor development through origami and meronce play therapy.For further researchers it is recommended toadding a variety of images in origami play therapy and taking a more approach to children when given play therapy.